2015
DOI: 10.1097/qai.0000000000000566
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Levels Are Increased in HIV Infection and May Drive Monocyte Activation

Abstract: Background Human immunodeficiency virus (HIV) infection is associated with increased cardiovascular risk, and this risk correlates with markers of monocyte activation. We have shown that HIV is associated with a prothrombotic monocyte phenotype, which can be partially mitigated by statin therapy. We therefore explored the relationship between oxidized LDL particles and monocyte activation. Methods We performed phenotypic analysis of monocytes using flow cytometry on fresh whole blood in 54 patients with HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 50 publications
(68 reference statements)
4
94
1
1
Order By: Relevance
“…Chronic innate immune activation in ART-treated HIV infection[26] may promote increases in LDL levels by altering how lipids are processed and transported, and immune activation likely enhances modification of these increased lipid molecules through the activity of reactive oxygen species (ROS) or enzymes such as lipoprotein-associated phospholipase A2 (Lp-PLA 2 )[57], rendering them more “inflammatory.” Modified lipid species, including oxidized forms of LDL (oxLDL)[58, 59] and HDL (HDLox) [60, 61], may contribute directly to monocyte[62] and endothelial cell activation in HIV disease, placing them on the mechanistic pathway for increased inflammation, immune activation, and CVD risk. Results from the ACTG substudy A5260s demonstrate that levels oxidized HDL are related to markers of inflammation and immune activation at baseline (IL-6, hsCRP, %CD38+HLA-DR+CD8+ T cells, sCD163) and following 96 weeks of ART (markers as before, including sCD14) [63].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic innate immune activation in ART-treated HIV infection[26] may promote increases in LDL levels by altering how lipids are processed and transported, and immune activation likely enhances modification of these increased lipid molecules through the activity of reactive oxygen species (ROS) or enzymes such as lipoprotein-associated phospholipase A2 (Lp-PLA 2 )[57], rendering them more “inflammatory.” Modified lipid species, including oxidized forms of LDL (oxLDL)[58, 59] and HDL (HDLox) [60, 61], may contribute directly to monocyte[62] and endothelial cell activation in HIV disease, placing them on the mechanistic pathway for increased inflammation, immune activation, and CVD risk. Results from the ACTG substudy A5260s demonstrate that levels oxidized HDL are related to markers of inflammation and immune activation at baseline (IL-6, hsCRP, %CD38+HLA-DR+CD8+ T cells, sCD163) and following 96 weeks of ART (markers as before, including sCD14) [63].…”
Section: Introductionmentioning
confidence: 99%
“…As early HIV-1 infection is characterized by persistent inflammation and enhanced tryptophan catabolism (22,(24)(25)(26)(27)42), we first evaluated the levels of several proinflammatory molecules and Kyn in plasma from the PHI, CHI, and HIV free subjects. Consistent with earlier reports (22,25,43), we found higher levels of IL-6, sCD14, IP-10, and Kyn in PHI and CHI subjects than HIV free donors (Fig.…”
Section: Loss Of Memory Cd4 T Cells During Hiv-1 Infection Involves Dmentioning
confidence: 99%
“…This inflammation is clinically relevant, since it has not been fully abrogated by long-term antiretroviral therapy (ART) (20)(21)(22)(23). Persistent inflammation during HIV-1 infection is associated with enhanced metabolic activity, which drives a Warburg-like effect on lipid, glucose, and amino acid pathways (22,(24)(25)(26)(27). The catabolism of an essential amino acid like tryptophan into kynurenine (Kyn), which is mediated by the indoleamine 2,3-dioxygenase 1 (IDO-1) expressed in dendritic cells (DCs) and monocytes, is increased in HIV-1-infected subjects (22,(28)(29)(30).…”
mentioning
confidence: 99%
“…oxLDL cholesterol is a proinflammatory form of LDL cholesterol that is often found within atheromatous plaques and contributes to the generation of foam cells, an integral step in instigating an acute coronary event (see below). Zidar et al showed that HIV-infected patients have both increased plasma levels of oxLDL, as well as increased monocyte expression of oxLDL receptors [30]. Plasma oxLDL levels were also correlated with markers of monocyte activation, suggesting that increased oxLDL levels serve as a driver of monocyte immune activation during HIV infection [30].…”
Section: Comorbid Conditionsmentioning
confidence: 99%
“…Zidar et al showed that HIV-infected patients have both increased plasma levels of oxLDL, as well as increased monocyte expression of oxLDL receptors [30]. Plasma oxLDL levels were also correlated with markers of monocyte activation, suggesting that increased oxLDL levels serve as a driver of monocyte immune activation during HIV infection [30].…”
Section: Comorbid Conditionsmentioning
confidence: 99%